A strategic framework for reusing partially treated wastewater in agriculture: Viability and sustainability prospects - Amjad Mizyed (Agricultural Water Management)
Water scarcity is a critical challenge in the Gaza Strip, where overexploitation and pollution have severely degraded groundwater resources. This study explores the feasibility of using reclaimed partially treated wastewater (RPTWW) for agricultural irrigation in the northern Gaza Strip as an alternative water source. A quantitative approach was applied, combining field data, farmer surveys, and simulation modeling using FAO’s CROPWAT 8.0 software. Water samples were analyzed to assess the chemical and microbiological quality of RPTWW. Results showed acceptable pH and nutrient levels, but elevated salinity, sodium, and chloride concentrations raised concerns about long-term soil degradation. The absence of fecal coliforms indicated suitability for restricted agricultural use. CROPWAT simulations showed that RPTWW could satisfy crop water demands during dry months if supported by efficient irrigation techniques. Farmer surveys indicated 77 % acceptance of RPTWW, primarily due to water scarcity, although concerns remain regarding health impacts and marketability. Findings support the integration of RPTWW into agricultural water management under controlled conditions. Key recommendations include raising farmer awareness, implementing drip irrigation systems, reducing nitrogen fertilizer use, restricting use for vegetables until water quality is assured, and monitoring groundwater quality. This research contributes to sustainable water management in conflict-affected regions and highlights the role of RPTWW in enhancing agricultural resilience and food security amid chronic water stress.